Propuesta de diseño de un sistema de tratamiento biológico de aguas residuales de la comunidad ¨El tejar Balbanera ¨ en Guamote. - Cazorla Vinueza, Ximena Rashell (2018)
To evaluate the first-hand assessment of the conditions of this community, the need arises to carry out the present investigation trying to fulfill the sixth objective of the Sustainable Development proposed by the United Nations "Clean Water and Sanitation" (UNDP, 2018) and to contribute to the development of the Good Living (El Buen Vivir ) proposed in our Constitution Art. 28, being a reference for the rest of communities and with the importance of the reuse of water, to promote the development and coordinated management of resources, to maximize economic, social and equitable welfare, without compromising sustainability of the ecosystems, guaranteeing a more reliable supply of irrigation water, the solution of a pollution problem due to the discharge of wastewater from the ¨El Tejar Balbanera¨ community is proposed. The community does not have sewerage, its gray water discharges are directly to the crops. The water in the toilets are discharged into septic tanks, which constitute the prymary of contamination affecting the health of the human being directly and indirectly, due to this the importance of considering an adequate final disposal to evacuate the residual waters of the community. The results of the characterization of the residual water when compared with similar investigations reaffirm the veracity of the present work, projecting with certainty the following proposal, in the initial phase a pretreatment: roughing by fine grids, additional a settler and finally a biological treatment of type Wetland with two series "Eichhornia Crassipes" and Totora "Typha spp." As a measure of low environmental impact and costs, water is obtained with reduction of the concentrations BOD_5 = 413.4 mg / L to final BOD_5 = 63.6 mg / L, complying with the permissible limits stipulated in the Official Register of the Ministerial Agreement in force 2015 (No. 097 A, ¨ Water quality criteria for agricultural irrigation ¨).